KORELASI PENGUASAAN KOSAKATA BIDANG BISNIS TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X MPLB SMK NEGERI 1 LUBUK SIKAPING KABUPATEN PASAMAN - Riri Septiani Agam; Farel Olva Zuve; Abdurahman Abdurahman; Vivi Indriyani (STKIP Pesisir Selatan, 2026)
This study aims to determine the correlation between business vocabulary mastery and expository text writing skills of class X MPLB students of SMK Negeri 1 Lubuk Sikaping. The type of research used is quantitative research with descriptive methods. The design in this study is correlational. The study population was 107 students, with a sample of 36 students determined through purposive sampling technique. Data were obtained through two types of tests, namely objective tests to measure business vocabulary mastery and performance tests to measure students' expository text writing skills. The results showed that students' business vocabulary mastery was in more than sufficient qualifications with an average count of 66.99, and students' expository text writing skills were also in more than sufficient qualifications with an average count of 70.37. The results of the correlation test showed that there was a significant positive relationship between business vocabulary mastery and students' expository text writing skills with degrees of freedom n-2 (36-2 = 34) and a significance level of 95%. H0 was rejected and H1 was accepted because the results of the hypothesis test showed t count> t table, namely 6.76> 1.69. This finding indicates that the higher the mastery of business vocabulary, the better the students' business-themed expository text writing skills.